Encyclopedia of modern ethnic conflicts - Rudolph, Joseph R. 1942- (Joseph Russell) (Gale virtual reference library, 2016)
This work uses case studies to explore acts of violence between ethnic or national communities inside individual states, making it an ideal reference to quickly gain an understanding of ethnic struggles.